Court of Flowers, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
A corner of the Court of Flowers, looking through Triumphal Arch, toward the Court of Reflections at the 1939 Golden Gate International Exposition on Treasure Island, San Francisco Bay